Daily tadalafil for the chronic phase of stuttering priapism: a case report - Massenio, Paolo (BMC Urol, 2018)
BACKGROUND: Recurrent (stuttering) ischemic priapism is a challenging clinical condition. Frequent recurrences result in frequent hospital admissions whereas treatment with a shunting procedure often results in erectile dysfunction. CASE PRESENTATION: A 22-year-old man with stuttering idiopathic priapism developed erectile dysfunction (IIEF-5 score 12) following a Winter’s shunt; he was given tadalafil, 5 mg/daily, for 6 months. This treatment resulted in progressive restoration of erectile function in the 6 months following the shunt as well as in preventing recurrence of priapic episodes over a 24-month follow-up. CONCLUSIONS: This is the first report in literature of chronic treatment of stuttering priapism with a phosphodiesterase-5 inhibitor being able not only to prevent recurrent priapic episodes but also to restore erectile function following a Winter’s shunt.